Alzheimer’s disease diagnosis via 5-layer Convolutional Neural Network and Data Augmentation - Shuangshuang Gao (EAI Endorsed Transactions on e-Learning, 2021)
OBJECTIVES: Alzheimer's disease (AD) is a progressive neurodegenerative disease with insidious onset and one of the biggest challenges in geriatrics. Because the cause of the disease is unknown and there is currently no cure, AD Early diagnosis is particularly important.